2022
DOI: 10.1088/1755-1315/1067/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Atmospheric Effects on the InSAR Measurements using GPS Data

Abstract: The effect of the atmospheric error in the spaceborne synthetic aperture radar (SAR) signal is more prominent in Malaysia due to its hot and wet conditions. Because the atmospheric error is believed to happen constantly in space and randomly in time, low-pass filtering in space and high-pass filtering in time is employed to measure it. However, with few scenes, the filtering technique’s reliability in removing atmospheric error may be insufficient, leading to erroneous surface deformation. Therefore, an extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Then, the interferogram was generated (Figure 2b,c, taking the fifth image position as an example). Taking the first scene image of each orbit in January 2020 as the super main image, 83,85,84,86,89,87,89,84,79,85, and 87 interference pairs were generated, respectively. After eliminating the interferograms with poor coherence, a multi-view coefficient of 1:5 was set in the range and azimuth directions to improve the processing interference quality.…”
Section: Methods 231 Sbas-insa Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the interferogram was generated (Figure 2b,c, taking the fifth image position as an example). Taking the first scene image of each orbit in January 2020 as the super main image, 83,85,84,86,89,87,89,84,79,85, and 87 interference pairs were generated, respectively. After eliminating the interferograms with poor coherence, a multi-view coefficient of 1:5 was set in the range and azimuth directions to improve the processing interference quality.…”
Section: Methods 231 Sbas-insa Technologymentioning
confidence: 99%
“…The climatic environment of the Kubuqi Desert features large temperature differences and high wind speeds and is characterized by frequent turbulence and scattering phenomena, thereby increasing atmospheric errors [86]. Even when atmospheric error corrections are added or interferometric pairs with atmospheric errors are removed, tropospheric errors are still not completely negligible [87]. After temporal cubic spline interpolation to produce a temporal resolution of 1 month, studies have shown that time scale interpolation can have a degrading effect on the accuracy of the results [88].…”
Section: Sources and Analysis Of Errors In Surface Deformation And Gr...mentioning
confidence: 99%